2023
DOI: 10.1186/s13018-023-03903-5
|View full text |Cite
|
Sign up to set email alerts
|

Regional versus general anesthesia in older patients for hip fracture surgery: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background The optimal anesthesia technique for older patients undergoing hip fracture surgery remains controversial. We performed a systematic review and meta-analysis of updated randomized controlled trials (RCTs) to assess whether regional anesthesia was superior to general anesthesia in hip fracture surgery. Methods We searched PubMed, EMBASE, Web of Science, and the Cochrane Central Register of Controlled Trials from January 2000 until April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…And reducing postoperative complications and hospitalization time are important indicators for accelerating postoperative rehabilitation. There are studies have reported that SA may be associated with a reduced incidence of postoperative complications, including death, deep vein thrombosis, pulmonary complications, and myocardial infarction (2,3,12,15,18), which aligns with our results. Selection bias is an obvious limitation of observational studies, resulting in unreliable results if improperly addressed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…And reducing postoperative complications and hospitalization time are important indicators for accelerating postoperative rehabilitation. There are studies have reported that SA may be associated with a reduced incidence of postoperative complications, including death, deep vein thrombosis, pulmonary complications, and myocardial infarction (2,3,12,15,18), which aligns with our results. Selection bias is an obvious limitation of observational studies, resulting in unreliable results if improperly addressed.…”
Section: Discussionsupporting
confidence: 92%
“…The choice of anesthesia affects patients' intraoperative hemodynamics and cardiopulmonary function, affecting their prognosis. Therefore, anesthesia has been controversial for older patients with lower limb fractures (2)(3)(4)(5)(6)(7)(8), but how anesthesia affects postoperative rehabilitation remains unknown.…”
Section: Introductionmentioning
confidence: 99%